2019
DOI: 10.1186/s12859-019-2751-3
|View full text |Cite
|
Sign up to set email alerts
|

A new massively parallel nanoball sequencing platform for whole exome research

Abstract: BackgroundWhole exome sequencing (WES) has been widely used in human genetics research. BGISEQ-500 is a recently established next-generation sequencing platform. However, the performance of BGISEQ-500 on WES is not well studied. In this study, we evaluated the performance of BGISEQ-500 on WES by side-to-side comparison with Hiseq4000, on well-characterized human sample NA12878.ResultsBGISEQ demonstrated similarly high reproducibility as Hiseq for variation detection. Also, the SNVs from BGISEQ data is highly c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 17 publications
0
46
0
Order By: Relevance
“…For example, the MGISEQ-2000 currently generates 1.44 TB of sequence data in a single run with a running cost of 10 USD/GB. Several recent studies have compared the performance of BGI sequencers with Illumina’s sequencers and showed that the BGI sequencers produced high-quality sequence data at lower or similar prices in studies of whole-exome [2,3], whole-genome [4][1], transcriptome [5,6], single-cell transcriptome [2,78], metagenome [9], and small RNA sequencing [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the MGISEQ-2000 currently generates 1.44 TB of sequence data in a single run with a running cost of 10 USD/GB. Several recent studies have compared the performance of BGI sequencers with Illumina’s sequencers and showed that the BGI sequencers produced high-quality sequence data at lower or similar prices in studies of whole-exome [2,3], whole-genome [4][1], transcriptome [5,6], single-cell transcriptome [2,78], metagenome [9], and small RNA sequencing [10].…”
Section: Introductionmentioning
confidence: 99%
“…This includes rolling circle replication and a novel DNA nanoball (DNB™) technology that leads to less CG bias compared to PCR assays and assures high signal to noise ratio (SNR) imaging for accurate base calling. BGISEQ is a reliable sequencing platform as recently reported by Xu and colleagues who compared BGISEQ to HiSEQ4000 platform and BGISEQ demonstrated similarly high reproducibility as HiSeq for variation detection [20]. In addition, Mak and colleagues reported a comparative performance of the BGISEQ-500 versus Illumina HiSeq2500 for WGS of ancient DNA [21].…”
Section: Discussionmentioning
confidence: 94%
“…Revolutionary NGS technologies have decreased the cost of genome sequencing, and they provide several hundred millions or billions of short DNA sequences on the surface of a flow cell for the study of protein-DNA interactions. In addition to Illumina's HiSeq, NextSeq, and NovaSeq platforms, Beijing Genomics Institute (BGI's) BGISEQ-500 and MGISEQ-2000 sequencing platforms have been extensively used in applications such as exon sequencing (12), single-cell RNA sequencing (13), small noncoding RNA analysis (14), and noninvasive prenatal testing (NIPT) (15). The technology underlying BGISEQ-500 or MGISEQ-2000 combines DNA nanoball (DNB) nanoarrays (16) with polymerase-based stepwise sequencing (DNBSEQ).…”
Section: Introductionmentioning
confidence: 99%